Synthesis of Gradient Copolymer Grafted Particle Brushes by ATRP - Wang, Zongyu; Liu, Tong; Zhao, Yuqi; Lee, Jaejun; Wei, Qiangbing; Yan, Jiajun; Li, Sipei; Olszewski, Mateusz; Yin, Rongguan; Zhai, Yue; Bockstaller, Michael R; Matyjaszewski, Krzysztof (Macromolecules, 2019)
Linear poly(n-butyl acrylate)-gradient-poly(methyl methacrylate) (PBA-grad-PMMA) copolymers and SiO2-g-PBA-grad-PMMA particle brushes were synthesized by activator regenerated by electron transfer atom transfer radical polymerization via a semibatch copolymerization method in which the methyl methacrylate (MMA) monomer was slowly fed to the polymerizing n-butyl acrylate (BA) solutions. The effects of initial BA concentration and the MMA feeding rate on the polymerization were investigated. Controlled gradient compositions were achieved at relatively low conversion, <20%. Two gradient copolymer particle brushes, with grafting densities of 0.55 and 0.126 chains/nm2, and one linear gradient copolymer were prepared with the same composition. Significant changes were observed after attaching the gradient copolymer ligands onto the surface of SiO2 nanoparticles, in both thermal and mechanical properties. Greater heterogeneity and microphase separation were introduced after the addition of SiO2 nanoparticles, and the nanocomposites displayed more complex glass transition temperature (T g) behavior and a broader T g range. An improvement in mechanical properties (strength and stiffness) was observed as the SiO2 nanoparticle content increased in gradient copolymer particle brushes; however, the damping property was compromised with increasing stiffness of the materials, especially under low frequency conditions.